Enhancing Bandung as a Global Destination for Coffee Tourism Innovation - Maspul, Kurniawan Arif (Centre for Tourism Studies and Journal Publication of Sekolah Tinggi Pariwisata Mataram, 2023)
Bandung, Indonesia, known for its colonial architecture and gastronomic offers, hopes to become a global coffee tourism destination. This study explores Bandung's coffee culture, including brewing methods and historical relevance, to develop personalized experiences and effective marketing strategies. Bandung may attract coffee fans while also supporting local coffee producers by focusing on coffee education, conducting specialty coffee events, and offering coffee vacation packages. Bandung's global appeal is further enhanced by digital marketing and virtual reality experiences. Understanding Bandung's coffee culture helps to preserve the city's legacy and solidifies its status as a top coffee tourism destination.